Conductivity Measurement for Control of a Biogas Plant - Richard Klein (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2018)
Nowadays in these modern times, when the majority of technologies are dependent on electrical energy, it is necessary to build new sources of energy ecologically and still improve their efficiency. One of the branches, which can contribute to ecology, is biogas plants. When biogas production methods are properly applied in them, these biogas plants have two advantages. One of them is the disposal of biowaste, the other is the production of green electricity in cogeneration units. In this article, steps which will enable better control of biogas transformations are listed. Therefore, they will contribute to the eco biogas production. The innovative approach involves adding new control variable. This variable can be shown in advance of the reaction, as evidenced by the charts. Results for evaluation were measured in the bioreactor during 20 experiments. Most (14) experiments were identical with residues from wine. The residue measurement was performed on three experiments in the remaining biomaterials. The course of production of methane always copied progress conductivity. This fact is evident from the graphs on Figs. 2–4. The methods used for data processing were: removal creeping values, statistic methods (median, average) and interpolation. It can be concluded from the results that the conductivity of digestate predicts specific production of biogas.